New Methylation Biomarker Panel for Early Diagnosis of Dysplasia or Cancer in High-Risk Inflammatory Bowel Disease Patients. Issue 12 (7th August 2018) - Azuara, Daniel; Aussó, Susanna; Rodriguez-Moranta, Francisco; Guardiola, Jordi; Sanjuan, Xavier; Lobaton, Triana; Boadas, Jaume; Piqueras, Marta; Monfort, David; Guinó, Elisabet; Moreno, Victor; Capellá, Gabriel; et al.
Abstract: Background: The risk of developing colorectal cancer (CRC) is increased in patients with inflammatory bowel disease (IBD) of the colon. The aim of the study was to evaluate the effectiveness of selected methylation gene panel for the early detection of CRC in high-risk IBD patients. Methods: In a discovery phase, 73 biopsies of 48 IBD patients (associated or not to CRC) were analyzed from genome-wide DNA methylation analysis using the Illumina Human Methylation 450K BeadChip. The panel of 5 genes selected ( EYA4, SLIT2, FLI1, USP44, and SND1 ) was validated prospectively using methylation-specific melting curve analysis in biopsies of diseased and adjacent healthy tissue of 203 patients: 38 with IBD and associated neoplasia, 81 patients with IBD (25 of them with high risk), 48 with sporadic CRC, and 36 healthy controls. Results: The prevalence of methylation was higher in patients with IBD and associated neoplasia (both in diseased and adjacent healthy tissue, 71% and 52%, respectively) than in healthy controls (2/36, 6%; P = 6.72E-05). Methylation in IBD patients at high risk of dysplasia or cancer was more frequently detected than in patients at low risk (92% vs 57%; odds ratio, 8.63; P = 0.001). EYA4 and SLIT2 were the markers most frequently methylated. Differences in methylation levels were more evident in healthy mucosa (82% vs 15% high vs low risk, respectively; P = 1.25E-05). Conclusions: Analysis of this panel of methylation markers may help in the early identification of colorectal dysplasia or cancer in high-risk IBD patients.